2003
DOI: 10.1023/a:1022385104386
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Recent studies suggest that ethylene is involved in signalling ozone-induced gene expression. We show here that application of ozone increased glucuronidase (GUS) expression of chimeric reporter genes regulated by the promoters of the tobacco class I beta-1,3-glucanases (GLB and Gln2) and the grapevine resveratrol synthase (Vst1) genes in transgenic tobacco leaves. 5'-deletion analysis of the class I beta-1,3-glucanase promoter revealed that ozone-induced gene regulation is mainly mediated by the distal enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Both the JA and ethylene signalling pathways have previously been shown to have a role in STS transcription [31-33,74,78,79]. Faurie et al [80] were able to show that co-treatment of Cabernet sauvignon suspension cells with methyl-jasmonate (MeJ) + Ethephon (ethylene) not only led to both a higher level of total stilbenes and VvSTS transcription compared to treatment with either elicitor alone, but also resulted in a biphasic pattern of transcription which was not observed in cells treated with MeJ or Ethephon only.…”
Section: Discussionmentioning
confidence: 99%
“…Both the JA and ethylene signalling pathways have previously been shown to have a role in STS transcription [31-33,74,78,79]. Faurie et al [80] were able to show that co-treatment of Cabernet sauvignon suspension cells with methyl-jasmonate (MeJ) + Ethephon (ethylene) not only led to both a higher level of total stilbenes and VvSTS transcription compared to treatment with either elicitor alone, but also resulted in a biphasic pattern of transcription which was not observed in cells treated with MeJ or Ethephon only.…”
Section: Discussionmentioning
confidence: 99%
“…PR gene expression is up-regulated in response to both pathogen attack and abiotic stresses (22,23), and previous studies have identified a central role for the Arabidopsis heterotrimeric G protein as an early mediator of plant stress signaling (24)(25)(26). The Arabidopsis genome encodes a single canonical heterotrimeric G protein ␣ and ␤ subunit and two ␥ subunits (27).…”
mentioning
confidence: 99%
“…The genetic variation of O 3 tolerance in these species has been attributed to a range of factors, including foliar phenolic composition ( 19 ), effective pathways of ascorbate-glutathione detoxification, remobilization of amino acids ( 20 ), genetic plasticity, chemical composition of foliar surface waxes ( 21 , 22 ), stomatal closure, and foliar structural traits, such as apoplastic volume, thickness, and leaf dry mass per unit area (LMA) ( 18 , 23 ). Model species such as Arabidopsis thaliana clearly indicate that O 3 tolerance is due to a unique set of alterations of various defensive mechanisms, e.g., signaling pathways, regulatory genes, plant hormones, antioxidants, and physiological processes (function and regulation of stomata) ( 24 , 25 ). These indicators of tolerance can be useful for individual plants or plant mixtures but are challenging in studies at evolutionary and population levels.…”
Section: Introductionmentioning
confidence: 99%